Machine perfusion preservation highlights from the Congress of the European Society of Organ Transplantation 2023 - Faria, Isabella; Vidgren, Mathias; Canizares, Stalin; Devos, Lene; Reichel, Katrin; Oniscu, Gabriel C.; Martins, Paulo N. (Artificial organs, 2024)
The 21st Congress of the European Society of Organ Transplantation (ESOT), held on September 17–20th, 2023, in Athens, Greece, was a pivotal event in transplantation, focusing on the theme “Disruptive Innovation, Trusted Care.” The congress attracted a global audience of 2 826 participants from 82 countries, emphasizing its international significance. Machine perfusion, as a groundbreaking technology in organ transplantation, was one of the central focuses of the conference. This year's meeting had a remarkable increase in accepted s on machine perfusion, evidencing its growing prominence in the field. The collective findings from these s highlighted the efficacy of machine perfusion in improving organ viability and transplant outcomes. Studies demonstrated improvements in graft survival and reduction in complications, as well as novel uses and techniques. Furthermore, the integration of machine perfusion with regenerative medicine and its application across multiple organ types were significant discussion points. The congress also highlighted the challenges and solutions in implementing machine perfusion in clinical settings, emphasizing the importance of practical training and international collaboration for advancing this technology. ESOT 2023 served as a crucial platform for disseminating scientific advancements, fostering practical learning, and facilitating international collaborations in organ transplantation. The congress underscored the evolution and importance of machine perfusion technology, marking a significant step forward in enhancing patient outcomes in the field of organ transplantation.